Human Resources Management in Improving the Professionalism of Police Members - Yohanes Ferry Cahya; Wahyu Romadhon; Sri Yanthy Yosepha (Goodwood Publishing, 2026)
Purpose: Optimization of operational management within the Law Enforcement Work Unit (Satker Gakkum) of the Indonesian National Police is crucial for enhancing effective investigative and enforcement capabilities. This study evaluates the operational management status in Satker Gakkum and offers ideas to enhance operational performance in facilitating law enforcement. Research Methodology: This qualitative study employed a descriptive analysis. Data were gathered via comprehensive interviews with Satker Gakkum members, direct observation, and document analysis. The study's findings reveal that the primary issues encountered include inadequate coordination across units, insufficient human resources and technology, and the ineffectiveness of standard operating procedures (SOPs). Results: These findings underscore the necessity for enhancements in resource management, the implementation of contemporary information technology, and the regular assessment and refinement of standard operating procedures (SOPs). Optimizing operational management is crucial for the effectiveness of investigations and law enforcement. This study underscores the significance of enhancing operational capacity through training, upgrading infrastructure, and fostering collaboration across relevant authorities. Conclusions: The proposed solutions enhance human resource quality, fortify information systems, and refine standard operating procedures to better adapt to investigations and law enforcement dynamics. Limitations: The qualitative methodology of this study, which focuses on gathering detailed information from a small sample within Satker Gakkum POLRI, limits its scope. Thus, the results may not apply to all Indonesian law enforcement agencies. Contributions: This study can help policymakers, police, and researchers enhance public safety institutions.